THE STUDY OF BILINGUAL MILIEU TOWARD THE STUDENT’S SPEAKING PERFORMANCE AT MODERN BOARDING SCHOOL: English - Muchsonny Muchsonny; Faisal Rahman; Rizky Hidayatullah (Prodi Tadris Bahasa Inggris, 2021)
This research aims to analyze bilingual milieu toward the student speaking performance The research method uses qualitative research . The data collection techniques are used to obtain the data on questionnaires response and interviews. The instruments in this research used questionnaires. The data analysis Method using descriptive method. This research is conducted by describing the results of observation and diagnostic of the student’s questioner and student’s activities. This research conducted in Modern Islamic Boarding School because it gives special program to more develop English and Arabic, one of primary program to develop language with bilingual milieu. Because bilingual milieu make students habitually in speaking foreign language. and bilingual milieu can improve the student’s performance in speaking English